Banking crisis prediction with differenced relative credit - Karlo Kauko; Eero Tölö (Bank of Finland, 2019)
Indicators based on the ratio of credit to GDP have been found to be highly useful predictors of banking crises. We study the difference in this ratio as an early warning indicator. We test a large number of different versions of the differenced credit-to-GDP ratio with data on Euro area members. The optimal time interval of the difference is about two years. Using the moving average of GDP instead of the latest annual data has little impact on forecasting performance. The indicator is a particularly promising choice at relatively short forecasting horizons, such as two or three years.
URN:NBN:fi:bof-201906061225
Keywords: G01; G17; G28; 330; banking crises; early warning indicators; differenced relative credit; credit intensity; countercyclical capital buffer